The Relationship Between Age, Smoking Habits, and Family History with Breast Cancer Incidence at Vina Estetica General Hospital in 2023 - Jeffrey22 Chua (Universitas Methodist Indonesia, 2025)
Background: Breast cancer is one of the cancers that ranks first in Indonesia with 68,858 cases and is still a problem in the world of health. Increasing age, having a smoking habit and a history of breast cancer in the family are risk factors for breast cancer. However, there are several studies that say that age, smoking habits and family history do not increase the risk of breast cancer. Purpose: The purpose of this study was to determine the relationship between age, smoking habits and family history with the incidence of breast cancer at Vina Estetica General Hospital in 2023. Research Methods: This study used the Chi Square test and the Binomial Logistic Regression statistical test with a cross-sectional approach to see the relationship between age, smoking habits and family history with the incidence of breast cancer at Vina Estetica General Hospital in 2023 with a sample size of 65 respondents. Results: In this study, the most respondents were found based on age> 35 years as many as 43 respondents (66.2%), based on smoking habits as many as 42 respondents (64.6%) and based on family history as many as 41 respondents (63.1%). relationship between age ≥ 35 years with the incidence of breast cancer with p-value Chi Square table 0.05 (dk 1) 3.841; RP 3.18; 95% CI 1.5779 - 6.3086. There is a relationship between smoking habits and the incidence of breast cancer with p-value Chi Square table 0.05 (dk 1) 3.841; RP 3.38; 95% CI 1.6823 - 6.7790. There is a relationship between family history and the incidence of breast cancer with p-value Chi Square table 0.05 (dk 1) 3.841; RP 3; 95% CI 1.5972 - 5.6742 and in the multivariate results obtained the dominant factors are age p-value 0.003, smoking habits p-value 0.012 and family history p-value 0.018. Conclusion: The results of the study found a relationship between age, smoking habits and family history with the incidence of breast cancer. With the dominant factor being age Keywords: Breast Cancer, Age, Smoking Habits, Family History.